Walking for transportation and built environment in Sao Paulo city, Brazil. (December 2019) - Florindo, Alex Antonio; Barbosa, João Paulo dos Anjos Souza; Barrozo, Ligia Vizeu; Andrade, Douglas Roque; de Aguiar, Breno Souza; Failla, Marcelo Antunes; Gunn, Lucy; Mavoa, Suzanne; Turrell, Gavin; Goldbaum, Moises
Abstract: Objective: To describe the profile of adults who walk for transportation in Sao Paulo city, and to explore the built environment features that are associated with transport walking. Material and methods: This study was a cross-sectional analysis of the Sao Paulo Health Survey dataset (n = 3145 people aged 18 years or older) that measured walking for transportation in a usual week by questionnaire. Residential addresses were geocoded and types and mix of destinations were assessed in 500 m and 1, 000 m buffers. We conducted Poisson regression to calculate the prevalence ratio and we used multilevel models to examine relationships between the built environment and walking for transportation. Results: People with higher levels of education and who were not obese were significantly more likely to walk for transportation. The cars or motorcycle ownership in families and aged 60 years old or more were significantly less likely to walk for transportation. After adjustment by social, demographic, and environmental variables, the main result showed that the highest tertiles of the mix of destinations within 500 m increased the likelihood of walking for transportation (OR = 1.40 CI95%1.01–1.93). The presence of public transportation stations within 1, 000 m was significantly associated with walking for transportation for 150 min or more per week (OR = 1.65 CI95%1.02–2.68). The presence of different types of destinations such as primary health care units, train or subway stations, bakeries, and the high density of supermarkets within 1, 000 m were significantly associated with some walking for transportation. The presence of bakeries in 500 m was strongly associated with some walking for transportation. Conclusions: The mix of destinations within 500 m and some types of destinations within 1, 000 m are important to promote walking trips in adults living in a megalopolis like Sao Paulo. These results can foster discussion of healthy cities in Latin American countries. Resumo: Objetivo: Descrever o perfil de adultos que caminham como transporte na cidade de São Paulo e verificar as variáveis de ambiente construído que estão associadas com caminhada como forma de transporte. Material e Métodos: Este foi um estudo transversal que utilizou dados do Inquérito de Saúde de São Paulo (n = 3145 pessoas com 18 anos ou mais de idade) que avaliou caminhada como forma de transporte em uma semana usual por questionário. Os endereços residenciais foram geocodificados e os tipos e a mistura de destinos foram avaliados em raios de 500 m e de 1.000 m. Realizou-se regressão de Poisson para calcular as razões de prevalência e modelos multiníveis para verificar as relações entre o ambiente construído e a caminhada como forma de transporte. Resultados: Pessoas com altos níveis de educação e que não eram obesas tiveram maiores razões de prevalência para caminhar como transporte. As pessoas com posse de carros ou motocicletas pelas famílias e com idade acima de 60 anos tiveram menores razões de prevalência para caminhar como forma de transporte. Depois do ajuste por variáveis sociais, demográficas e ambientais, o principal resultado mostrou que altos tercis de mistura de destinos dentro de 500 m aumentaram as chances de caminhada como forma de transporte (OR = 1, 40 IC95%1, 01-1, 93). A presença de estações de transporte público dentro de 1, 000 m foi significativamente associada com caminhada como transporte por 150 minutos ou mais por semana (OR = 1, 65 IC95%1, 02-2, 68). A presença de diferentes tipos de destinos como unidades básicas de saúde, estações de trem ou metrô, padarias e altas densidades de supermercados dentro de 1.000 m foram significativamente associadas com caminhada como forma de transporte. A presença de padarias dentro de 500 m foi fortemente associada com caminhada como forma de transporte. Conclusão: A mistura de destinos dentro de 500 m e alguns tipos de destinos dentro de 1.000 m são importantes para promover viagens de caminhadas em adultos em uma megalópole como São Paulo. Estes resultados podem fomentar a discussão sobre cidades saudáveis em países da América Latina. Resumen: Objetivo: Describir el perfil de adultos que caminan como forma de transporte en la ciudad de São Paulo y verificar las variables de ambiente construido que están asociadas a la caminata como forma de transporte. Material y Métodos: Este fue un estudio transversal que utilizó datos de la investigación de Salud de São Paulo (n = 3.145 personas con 18 años o más de edad) que evaluó caminata como forma de transporte en una semana usual por cuestionario. Las direcciones residenciales fueron geocodificadas. Los tipos y la mezcla de destinos fueron evaluados en radios de 500 m y 1.000 m. Se realizó regresión de Poisson para calcular las razones de prevalencia y modelos multinivel para verificar las relaciones entre el ambiente construido y la caminata como forma de transporte. Resultados: Personas con altos niveles de educación y que no eran obesas tuvieron mayores razones de prevalencia de caminata como transporte. Las personas que poseen automóviles o motocicletas por las familias y con edad superior a 60 años tuvieron menores razones de prevalencia de caminata como forma de transporte. Después del ajuste por variables sociales, demográficas y ambientales, el principal resultado mostró que los terciles más altos de mezcla de destinos dentro de 500 m hicieron más probable la caminata como forma de transporte (OR = 1, 40 IC95%1, 01-1, 93). La presencia de estaciones de transporte público dentro de 1.000 m fue significativamente asociada a la caminata como transporte por 150 minutos o más por semana (OR = 1, 65 IC95%1, 02-2, 68). La presencia de diferentes tipos de destinos como unidades básicas de salud, estaciones de tren o metro, panaderías y altas densidades de supermercados dentro de 1.000 m fueron significativamente asociadas a la caminata como forma de transporte. La presencia de panaderías dentro de 500 m fue fuertemente asociada a la caminata como forma de transporte. Conclusión: La mezcla de destinos dentro de 500 m y algunos tipos de destinos dentro de 1.000 m son importantes para promover desplazamientos por caminatas en adultos en una megalópolis como São Paulo. Estos resultados pueden fomentar la discusión sobre ciudades saludables en países de América Latina. Highlights: The mix of destinations is associated with walking trips in 500 m. Transportation stations are associated with regular transport walking in 1, 000 m. Bakeries, health units, supermarkets are associated with walking trips in 1, 000 m. These results can use to promote walking trips in cities like Sao Paulo.